Using role-playing games to broaden engineering education. Issue 4 (2nd May 2017) - McConville, Jennifer R.; Rauch, Sebastien; Helgegren, Ida; Kain, Jaan-Henrik
Abstract : Purpose: In today's complex society, there is an increasing demand to include a wider set of skills in engineering curricula, especially skills related to policy, society and sustainable development. Role-playing and gaming are active learning tools, which are useful for learning relationships between technology and society, problem solving in complex situations and communication. However, use of these learning methods in higher education, and in engineering particularly, is limited. The purpose of this study was to test the effectiveness of a role-playing game for learning about complexities related to sustainable water and sanitation management within a civil engineering curriculum. Design/methodology/approach: The game has been used during three consecutive years in a Masters' level course. Surveys and course evaluations were used to evaluate the effectiveness of this method from both teacher and student perspectives. Findings: The results show that students gained knowledge on complex subjects, and both teachers and students had positive experiences. Better integration of the game within the rest of the course could strengthen its effectiveness. Originality/value: The experiences gained from this study should assist others in the development and use of such active learning techniques in higher education.